Specific immunity proteomic profile of the skin mucus of Antarctic fish Chionodraco hamatus and Notothenia coriiceps - Shaojun Huang; Ruonan Jia; Ruiqin Hu; Wanying Zhai; Shouwen Jiang; Wenhao Li; Faxiang Wang; Qianghua Xu (Journal of Fish Biology, 2021)
The white‐blooded Antarctic icefish is the only known vertebrate lacking oxygen‐transporting haemoglobins. Fish skin mucus, as the first line of defence against pathogens, can reflect fish welfare. In this study, we analysed the skin mucus proteome profiles of the two Antarctic fish species, the white‐blooded Antarctic icefish, Chionodraco hamatus , and the red‐blooded Antarctic fish, Notothenia coriiceps , unfolding the different proteins by liquid chromatography coupled with tandem mass spectrometry isobaric tags for relative and absolute quantitation (iTRAQ) technology. Of the 4444 totally identified proteins, 227 differentially expressed proteins (DEPs) were found in the comparison between C. hamatus and N. coriiceps , of which 121 were upregulated and 106 were downregulated in the icefish. In the Kyoto Encyclopedia of Genes and Genomes pathway annotation, we found two pathways “Legionellosis” and “Complement and coagulation cascades” were significantly enriched, among of which innate immune candidate proteins such as C3, CASP1, ASC, F3 and C9 were significantly upregulated, suggesting their important roles in C. hamatus immune system. Additionally, the DEP protein–protein interaction network analysis and “Response to stress” GO category provided candidate biomarkers for deep understanding of the distinct immune response of the two Antarctic fish underlying the cold adaptation.